Remainder? Part-4

Find the remainder when 3 4 n 2 + 2 6 n 3 + 1 \large 3^{4n-2} + 2^{6n-3} + 1

is divided by 17, where n n is a positive integer.


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Dec 26, 2019

Similar solution as @Tom Engelsman's

N = 3 4 n 2 + 2 6 n 3 + 1 = 3 2 ( 2 n 1 ) + 2 3 ( 2 n 1 ) + 1 = 9 2 n 1 + 8 2 n 1 + 1 Since 2 n 1 is odd = ( 9 + 8 ) k = 1 2 n 2 ( 1 ) k 9 k 8 2 n 2 k + 1 = 17 k = 0 2 n 2 ( 1 ) k 9 k 8 2 n 2 k + 1 \begin{aligned} N & = 3^{4n-2} + 2^{6n-3} + 1 \\ & = 3^{2(2n-1)} + 2^{3(2n-1)} + 1 \\ & = \blue{9^{2n-1} + 8^{2n-1}} + 1 & \small \blue{\text{Since }2n-1 \text{ is odd}} \\ & = \blue{(9+8) \sum_{k=1}^{2n-2} (-1)^k 9^k \cdot 8^{2n-2-k}} + 1 \\ & = 17 \sum_{k=0}^{2n-2} (-1)^k 9^k \cdot 8^{2n-2-k} + 1 \end{aligned}

Therefore, N m o d 17 = 1 N \bmod 17 = \boxed 1 .

Forgot the (-1)^k term in the summation, Chew-Seong. The irreducible polynomial factor has alternating signs between terms!

tom engelsman - 1 year, 5 months ago

Log in to reply

Yes, thanks.

Chew-Seong Cheong - 1 year, 5 months ago

Log in to reply

No prob! Very Happy New Year too....both climbin' our way to our 2nd 1M-points!

tom engelsman - 1 year, 5 months ago
Tom Engelsman
Dec 25, 2019

Let us rewrite the above expression according to:

3 4 n 2 + 2 6 n 3 + 1 = ( 3 2 ) 2 n 1 + ( 2 3 ) 2 n 1 + 1 = 9 2 n 1 + 8 2 n 1 + 1 3^{4n-2} + 2^{6n-3} + 1 = (3^2)^{2n-1} + (2^3)^{2n-1} + 1 = 9^{2n-1} + 8^{2n-1} + 1 (i)

Since we have 8 8 and 9 9 both being raised to an odd integer power in (i), we can factor according to:

( 9 + 8 ) [ Σ k = 0 2 n 2 ( 1 ) k 9 2 n 2 k 8 k ] + 1 (9+8) \cdot [\Sigma_{k=0}^{2n-2} (-1)^k \cdot 9^{2n-2-k} \cdot 8^{k}] + 1 (ii)

Since 17 ( 9 + 8 ) [ Σ k = 0 2 n 2 ( 1 ) k 9 2 n 2 k 8 k ] 17 | (9+8) \cdot [\Sigma_{k=0}^{2n-2} (-1)^k \cdot 9^{2n-2-k} \cdot 8^{k}] in (ii), the remainder is just 1 . \boxed{1}.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...